Pengaruh Kompetensi Guru dan Motivasi Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi Kelas XI di MAN 3 Jombang - Imroatus Sholikah; Ninik Sudarwati (YASIN, 2026)
Although student learning outcomes have received attention in various previous studies, studies that specifically discuss the simultaneous effect of teacher competence and learning motivation on student learning outcomes in economics at the madrasah level remain limited. This study aims to analyze the effect of teacher competence and learning motivation on the learning outcomes of eleventh-grade students in economics at MAN 3 Jombang. This study used a quantitative approach with a survey design. The research respondents were eleventh-grade students selected through the sampling technique established in the study. Data were collected using questionnaires and documentation, and were then analyzed using multiple linear regression. The results showed that teacher competence had a positive and significant effect on student learning outcomes, learning motivation had a positive and significant effect on learning outcomes, and teacher competence and learning motivation simultaneously had a positive and significant effect on student learning outcomes. These findings contribute to the development of educational studies, particularly regarding the role of teacher competence and learning motivation in supporting students’ academic achievement in economics. The conclusion of this study affirms that improving teacher competence and strengthening learning motivation are important factors in enhancing student learning outcomes. The implications of this study include theoretical contributions to the development of educational literature as well as practical implications for madrasahs in improving teaching quality and designing more effective learning strategies.